The Road Not Taken (Comparative & International Education Series, 2022)
As a blessed person who has witnessed the beauty of taking the road not taken, my heart is pounding to share my experience as a former international student who took a less traveled road.While I currently work as a faculty member in the field of education at a U.S. higher education institution, my journey as an educator began in fall 2003, the semester that I came to Michigan State University (MSU) from South Korea to pursue a graduate degree in counseling. Although I knew I was privileged to leave my home country to study abroad and I was filled with pride that I had decided to take a less traveled road by studying counseling in the United States, which was extremely rare for someone from Korea at that time, my first day was horrible and the second day was even worse.